Analysis of the Migration Phenomenon of Physicians from Romania - Simona-Andreea APOSTU; Maria Denisa VASILESCU; Ruxandra CHIVU (Communications of International Proceedings, 2022)
The physician’s migration from Romania has registered an ascending trend over time, this phenomenon having negative effects on population health, but also on health system efficiency. Using the Principal Components Analysis we highlighted the link between the number of Current Professional Certificates and the variables refering to the economic situation of the destination countries where physicians choose to leave. Data were provided by the Romanian College of Physicians and the Eurostat database, and SAS and Excel software were used for the analysis.
Keywords: brain drain; physicians’ migration; Principal Component Analysis; Romania